Troubleshooting rubber problems - Sommer, John G. (Hanser Publishers, 2013)
Many challenges confront the rubber technologist in the development, manufacture, and use of rubber products. These challenges include selecting and combining materials to form rubber compounds suitable for processing, successfully operating a range of manufacturing equipment, and meeting product performance in difficult and diverse environments. Case studies and literature references relate problem solutions to the everyday experience of the rubber technologist. From materials to processes to products, this book identifies many different rubber-related problems and suggests approaches to solve them. Contents: . TSE and TPE Materials, Compounds, Processes, and Products . TSE Materials and Compounds . TSE Processes and Equipment . TSE Products . TPE Materials and Compounds . TPE Processes and Equipment . TPE Products.